U–Pb ages of detrital zircon grains for the Canastra Group and Passos Nappe units and U–Pb and Lu–Hf isotope analyses from orthogneisses: Provenance and tectonic implications, southern Brasília Belt, Brazil - Silva, Alex J. Choupina A. [UNESP]; Simões, Luiz Sérgio A. [UNESP]; DuFrane, Scott Andrew; Sá Alkmin, Leonardo Azevedo; Cerri, Rodrigo Irineu [UNESP] (Elsevier, 2020)
The age and tectonic setting of Mesoproterozoic to Neoproterozoic covers that occur along the southwestern margins of the São Francisco Craton (SFC) are still uncertain. This study reports new 207Pb/206Pb LA-ICPMS ages of detrital zircon grains from metasedimentary rocks of the Passos Nappe units and Canastra Group, and combined U–Pb and Lu–Hf analyses on igneous zircon from orthogneisses within the metasedimentary units. The U–Pb age spectra of detrital zircon grains of the Canastra Group comprises a wide range from ∼1.30–2.71 Ga with a significant Rhyacian component source (∼2.1 Ga). The second major source is represented by Statherian grains (∼1.6–1.7 Ga), and are similar to the Statherian interval at Espinhaço Basin. The youngest ages fall around ∼1.30 Ga. This peak age is compatible with the initial extension and sedimentation of the Carandaí and Middle Espinhaço basins, which mark the second intracratonic rifting of the São Francisco Craton. Zircon grains from the metasedimentary rocks the Passos Nappe yielded a very prominent Rhyacian peak at ca. 2.10 Ga with some Statherian and Neoarchean contributions. All samples from the metasedimentary units show a prominent peaks at ca. 2.10 Ga, suggesting that most sedimentary sources derived from a Rhyacian substratum similar to the Mineiro belt, Natividade-Cavalcanti block, Campinorte Complex and Juiz de Fora Complex. Rhyacian age is compatible with U-Pb crystallization ages of felsic orthogneisses (2122 ± 67 and 2117 ± 23), enclosed as tectonic lenses in the Passos Nappe and the Canastra Group. These rocks show initial εHf(t) values between +2.1 to −13.0 and +10.0 and −1.8, indicating that these orthogneisses are derived from Rhyacian granitic rocks, which were formed either by fractionation or re-melting of juvenile magmas, and by the reworking of more ancient, mainly Archean crust. The new data and regional geologic correlations suggest evidence of Paleoproterozoic terrain in the southwestern margin of the SFC.
Keywords: Lu–Hf isotopes; Passos Nappe units and Canastra Group; Southern Brasília belt; U–Pb geochronology